Draft Five Year Plan 1978-83 Forest Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
With over one third of the geographical area of Madhya. Pradesh under forest cover, the forestry sector holds the key to the prosperity and future economic development of the state. the Forest contribute 14-16% of the total receipts of the state Government, engages 71 million man-days of the working population of the state (in addition to providing regular jobs to over 27,000 people), and protect the vital upper catchments of the major river systems on which depends the agricultural prosperity of not only the state it self, but of the adjoining states too.
Government of Madhya Pradesh, Planning, Economics and Statistics Department